Programmed cell death ligand 1 and tumor‐infiltrating lymphocyte status in patients with renal cell carcinoma and sarcomatoid dedifferentiation. Issue 24 (22nd August 2017) - Kawakami, Fumi; Sircar, Kanishka; Rodriguez‐Canales, Jaime; Fellman, Bryan M.; Urbauer, Diana L.; Tamboli, Pheroze; Tannir, Nizar M.; Jonasch, Eric; Wistuba, Ignacio I.; Wood, Christopher G.; Karam, Jose A.
Abstract : BACKGROUND: The immune profile of sarcomatoid renal cell carcinoma (sRCC), including the programmed cell death ligand 1 (PD‐L1) and programmed cell death 1 (PD‐1) status, has not been well characterized. METHODS: An immunohistochemical digital analysis of PD‐L1, PD‐1, CD4, and CD8 was performed on nephrectomy specimens from 118 sRCC patients and 92 nonsarcomatoid clear cell renal cell carcinoma (ccRCC) patients. The clinical characteristics of the population were compared between sRCC and ccRCC. Overall survival was estimated, and comparisons were made between PD‐L1–positive and PD‐L1–negative groups as well as tumor‐infiltrating lymphocyte (TIL)–high and TIL‐low groups. RESULTS: The PD‐L1 H‐score of sRCC (mean, 3.7; range, 0‐192.1) was significantly higher than the score of grade 4 ccRCC ( P  = .001), and 41.3% of sRCC cases showed a PD‐L1 H‐score ≥ 10. The PD‐1–positive cell density was significantly higher in sRCC versus ccRCC within the tumor and at the invasive front. The intratumoral CD8‐positive cell density was significantly higher in sRCC versus ccRCC. Forty‐one percent in the sarcomatoid component of sRCC and 8% in the epithelioid component of sRCC had an adaptive immune resistance phenotype (PD‐L1–positive and TIL‐positive), whereas only 1% in ccRCC had the type I phenotype. CONCLUSIONS: sRCC showed higher PD‐L1 expression and higher PD‐1– and CD8‐positive cell density than grade 4 ccRCC. The results indicate a notable immunosuppressive environment in sRCC. Despite advances in the treatment of advanced‐stage renal cell carcinoma, sRCC still has a poor prognosis. This work describes highly immunosuppressive characteristics of sRCC in comparison with an appropriate ccRCC control. The results suggest PD‐1/PD‐L1 blockade therapy as a potential therapeutic approach for sRCC. Cancer 2017;123:4823‐31 . © 2017 American Cancer Society . Abstract : Sarcomatoid renal cell carcinoma expresses programmed cell death ligand 1 (PD‐L1) more frequently and contains more tumor‐infiltrating lymphocytes, including programmed cell death 1 (PD‐1)–positive T cells, than grade 4 clear cell renal cell carcinoma. Many sarcomatoid renal cell carcinoma cases carry an adaptive immune resistance phenotype, and PD‐1/PD‐L1 blockade therapy could be a promising therapeutic approach.